Justice League, Darkseid War. The power of the gods. - Tomasi, Peter (DC Comics, 2016)
Darkseid has been defeated, killed by the Anti-Monitor. Out of this monster's death, a new set of gods has risen--Earth's Justice League, transformed by new abilities they've never imagined. Life and death, all the knowledge and power in the universe are the Justice League's tools to wield. They can reshape the world with just a thought, but their new gifts come with a hefty price. If Earth's greatest heroes can't find their way back to their humanity, they may bring about their own destruction.